Tolerance Development Model for Students of Dayah Salafiyah in Aceh - Suyanta, Sri; Saifuddin, Saifuddin; Bahri, Syamsul (Jurnal Ilmiah Peuradeun, 2024)
This study delved into the model of tolerance among Acehnese Dayah Salafiyah students, aiming to bridge the gap in understanding their perceived tolerance amidst societal stigmas. Data from two Dayah Salafiyah, Dayah Darussalam Labuhan Haji, and Dayah Ummul Ayman Samalanga, were gathered through participant observation, in-depth interviews, and document studies. Data analysis including data reduction, presentation, and conclusion. This analysis was conducted continuously throughout the research, from data collection to conclusion. Findings indicated a tendency towards passive tolerance among students, which aligned with Islamic principles of tasamuh and was integrated into their education. Despite negative perceptions, students exhibited principles of equality, harmony, and respect for diversity, challenging accusations of intolerance. However, shortcomings existed in exploring contemporary tolerance issues, especially in teacher involvement and understanding beginner-level students. Encouraging the implementation of existing tolerance is vital for Dayah’s internal and external stakeholders. These findings deepened the understanding of tolerance models in Aceh’s Dayah Salafiyahs, warranting consideration by researchers in future studies. Additionally, the authors recommend that other researchers consider the results of this study as a reference for their research or surveys, emphasizing the need for developing tolerance indices tailored to the unique characteristics of each region to demonstrate tolerance towards others.